Ballast water management in Small Island Developing States (SIDS) of the Caribbean - Richmond Santani Basant; Dayne Buddo; Azad Mohammed; Hamish Asmath; Judith Gobin; La Daana K. Kanhai (Marine Policy, 2026)

Abandoned, lost and otherwise discarded fishing gear in the Caribbean SIDS of Trinidad and Tobago - La Daana K. Kanhai; Tricia Lovell; Hamish Asmath; Haraldur Einarsson; Elias Keller; Isabel Richter; Joel Baziuk (Marine Pollution Bulletin, 2026)

Terrestrial Laser Scanning for the Estimation of Above Ground Biomass of Mangrove Roots by Modelling Them as Inverted Trees - Hamish Asmath; John Agard; Toby Jackson; Nikia Gooding; Gerard Alleng; Graham King; Michael Oatham; Farrah Mathura (Wetlands, 2025)
The complex root systems of mangroves such as Rhizophora spp. can hold up to 40% of the total tree biomass yet have usually been neglected in the assessment of the aboveground biomass (AGB). Traditional measurements of AGB can be laborious, costly, time consuming, and require the destruction of the tree. Terrestrial laser scanning (TLS) has increasingly been applied to recreate the architecture of trees to reduce the need for destructive sampling. Modelling Rhizophora mangle L. prop and aerial roots as inverted trees allowed recreation of the volumes using a largely automated methodology. Trees were scanned using a Leica (Switzerland) BLK360 TLS, scans registered and combined, individual tree point clouds extracted and cleaned, the root and trunk point clouds automatically disaggregated, the branches and leaf point cloud separated using auto segmentation techniques, and finally then the volume of the woody fraction of the tree generated in TreeQSM. Two trees were scanned and destructively harvested to assess the modelled wood volume and weight. Wood volume was overestimated by 6.18 and 8.31%, while AGB was overestimated by 2.07 and 2.93%. The robustness of these results demonstrate that this methodology can be applied to improve the estimation of mangrove aboveground biomass. It can facilitate the development of site and species specific allometric equations, that would contribute towards the improved accuracy of carbon estimates at the landscape scale.

Temporospatial dynamics and public health significance of bacterial flora identified on a major leatherback turtle ( Dermochelys coriacea ) nesting beach in the Southern Caribbean - Ayanna Carla N. Phillips; Johanna Coutou; Stacy Rajh; Neville Stewart; Antonio Watson; Adam Jehu; Hamish Asmath; Francis Dziva; Chandrashekhar Unakal; Ridley Holder; Raymond Raoul Carthy (Marine Ecology, 2017)
Grande Riviere beach, on the island of Trinidad, supports the largest nesting population of leatherback turtles in the Caribbean region. Throughout the nesting season, nests are naturally disturbed by newly nesting females, resulting in egg breakage and loss of some nest viability. This environment is ideal for the growth and proliferation of microorganisms. The range of bacterial flora present in beach sand and egg shells was examined, with emphasis on bacteria that may pose a threat to public and animal health. The extent to which the bacterial load and genera on the beach changed throughout the season was also assessed. Twenty‐five genera were identified, with Pseudomonas spp. found to be the most predominant environmental bacteria. Four genera identified possess zoonotic potential, while five additional genera are known to be of public and animal health significance. Distinct shifts in the density and distribution of bacteria were observed along the beach from early to peak nesting season. Shifts were seen across heavily traversed zones, thus highlighting the potential exposure threats posed to beach visitors and animals alike. Further studies aimed at speciating this population of bacteria, as well as isolating potential fungal pathogens may mitigate this threat. Identification of bacterial agents that are specifically pathogenic to leatherback turtles, turtle eggs, hatchlings and those who may interact with these animals will serve to enhance and guide efforts to better conserve this species and protect the health of all who visit this ecologically significant site.

Flood-risk mapping for storm surge and tsunami at Cocos Bay (Manzanilla), Trinidad - Junior Darsan; Hamish Asmath; Adam Jehu (Journal of Coastal Conservation, 2013)